An Honorable Break from Besa: Reorienting Violence in the Late Ottoman Mediterranean - Blumi, Isa (European journal of Turkish studies, 2014)
This is a study of the shifting fortunes of Ottoman western Balkan regions (represented here in their main towns) at the end of imperial rule. It reads the evidence of certain internal dynamics to reconsider what are the animating forces at work during a period of state reorientation such as that of 1878 to 1918. Using the cases of the Ottoman western Balkans as extensions of broader regional interactions between (not so neatly distinctive) state and subject actors, it becomes clear that the origins of certain kinds of social upheaval are linked to local socio-economic forces directly affiliated with administrative reforms. What is often missing in early readings of these reforms is that many were adopted to harness local practices of conflict resolution. As argued throughout, the local forces engaging with presumably distinct state actors would ultimately influence new regional conditions that were often registered as indigenous principles or “values”. The manner in which state authorities tried to co-opt these local practices often proved violent. Such violence invariably appears in the documents. Where this paper seeks to go, however, is to highlight how the violence alone cannot serve as our focus to better understand how change is brought to the region. Rather, it aims to show how indigenous forms of mediating violence, often through honor codes, as in the Albanian case studied here, known as besa, we can begin to better understand the complicated intersections of institutional changes and indigenous actors.